TAX SUPPORT FOR PRIVATE INVESTMENT IN EDUCATION - S. N. Rukina; K. A. Gerasimova; A. S. Takmazyan; K. N. Samoylova (Вестник университета)
The successful implementation of the national project “Education” is associated not only with the effective use of budget funds, but also with attraction of private investment in the education system. The article substantiates the relevance of this issue for the Russian regions, due to the preferential financing of current spending on education from the consolidated budgets of the subjects of the Russian Federation, various provision of educational institutions, demographic processes. The analysis of the current tax legislation, statistical indicators has allowed propose measures to enhance the stimulating role of individual elements of corporate income tax and personal income tax, which will contribute to the growth of investments of organizations and individuals in education